Fe3O4-CNT / MgO-ATP / SA electrode material and application thereof
Through the preparation of Fe3O4-CNT/MgO-ATP/SA electrode materials, the problem of insufficient performance of auxiliary electrode materials in electric repair technology is solved, the effect of efficient removal of heavy metal ions in the soil is achieved, and the risk of secondary pollution is reduced.
Patent Information
- Application Number
- CN202411500826.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-25
AI Technical Summary
In the existing electric repair technology, auxiliary electrode materials have poor conductivity, insufficient stability, and are prone to corrosion, making it difficult to effectively remove heavy metal ions in the soil, and there is a risk of secondary pollution.
Fe3O4-CNT/MgO-ATP/SA electrode material is prepared by hydrothermal reaction and magnetic adsorption technology to form an auxiliary electrode material with high conductivity, excellent adsorption performance and corrosion resistance. The magnetic properties and MgO- of Fe3O4-CNT are used. The adsorption capacity of ATP improves the efficiency of electrochemical reactions and realizes magnetic recovery processing.
It realizes efficient removal of heavy metal ions, improves current response and mechanical strength during the electric repair process, reduces the risk of secondary pollution, and the material is environmentally friendly and durable.
Smart Images

Figure CN119281805A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of soil remediation, and in particular to a Fe3O4-CNT / MgO-ATP / SA electrode material and application thereof. Background Art
[0002] With the rapid development of industrialization, soil pollution is becoming increasingly serious, especially heavy metal pollution, which poses a major threat to the environment and human health. Although traditional physical, chemical and biological remediation technologies have alleviated soil pollution to a certain extent, their remediation efficiency is low, the cost is high, and they are prone to secondary pollution. In recent years, electrokinetic remediation technology has attracted widespread attention because it can effectively remove heavy metal ions from the soil. However, during the electrokinetic remediation process, the performance of the auxiliary electrode has an important influence on the remediation efficiency. Existing electrode materials generally have problems such as poor conductivity, insufficient stability, and susceptibility to corrosion, which makes it difficult to meet the needs of long-term, efficient and low-cost remediation. Therefore, the development of an auxiliary electrode material with high conductivity, excellent adsorption performance, strong corrosion resistance and environmental protection has become an urgent problem to be solved in the current field of soil pollution remediation.
[0003] Most of the current auxiliary electrodes, such as the Chinese invention patent CN 114029332 A which discloses a device and method for electrically repairing cadmium-contaminated soil using an activated graphene-assisted electrode, have the following defects: the combination of activated graphene and filter paper may suffer from mechanical wear or structural damage during long-term use, which may affect the durability and efficiency of the repair effect and cause secondary pollution to water and soil. Summary of the invention
[0004] The problem in the prior art is that the conventional auxiliary electrodes used in the electrokinetic remediation technology have poor mechanical properties and it is difficult to achieve a 70% removal effect on heavy metal ions in the soil. In view of the above problems, the present invention provides a Fe3O4-CNT / MgO-ATP / SA electrode material, and the preparation method thereof comprises the following steps:
[0005] (1) ATP powder and soluble magnesium salt undergo hydrothermal reaction under alkaline conditions, the reaction liquid is separated into solid-liquid to obtain a solid product, and the obtained solid product is placed at high temperature and calcined in an air atmosphere to obtain MgO-ATP loaded with magnesium oxide particles;
[0006] (2) The acidified carbon nanotubes and Fe 2+ , Fe 3+ The soluble salt and the surfactant are mixed evenly in the aqueous solution, the pH of the solution is adjusted to be alkaline, and the reaction is stirred until the iron oxide is adsorbed on the tube wall of the acidified carbon nanotube, and the solid product in the solution is collected by magnetic attraction using a magnet to obtain Fe3O4-CNT;
[0007] (3) mixing and dispersing MgO-ATP and Fe3O4-CNT in deionized water to obtain a Fe3O4-CNT / MgO-ATP suspension;
[0008] (4) The SA aqueous solution is added dropwise to the Fe3O4-CNT / MgO-ATP suspension while stirring. After the reaction is completed, the reaction solution is filtered, and the obtained filter cake is freeze-dried and heat-treated at high temperature under a nitrogen atmosphere.
[0009] Preferably, the temperature of the hydrothermal reaction in step (1) is not less than 120° C., and the hydrothermal time is not less than 6 hours.
[0010] Preferably, the high-temperature calcination temperature in step (1) is not higher than 500° C., and the calcination time is not less than 2 hours.
[0011] Preferably, the acidified carbon nanotubes in step (2) are products obtained by adding carbon nanotubes to a dilute nitric acid aqueous solution for oxidation.
[0012] Preferably, the surfactant is SDS.
[0013] Preferably, in step (3), the mass ratio of MgO-ATP to Fe3O4-CNT is 0.1-2:1.
[0014] Preferably, in step (3), the mass ratio of MgO-ATP to Fe3O4-CNT is 1:1.
[0015] Preferably, the mass ratio of SA in step (4) to MgO-ATP and Fe3O4-CNT in step (3) is 1:1:1.
[0016] Preferably, the temperature of the high temperature heat treatment in step (4) is not higher than 450°C, and the heat treatment time is not less than 2 hours.
[0017] Preferably, the freeze-drying time in step (4) is not less than 24 hours.
[0018] The present invention has the following beneficial effects:
[0019] (1) The present invention encapsulates magnesium oxide modified attapulgite (MgO-ATP) and ferroferric oxide magnetized carbon nanotubes (Fe3O4-CNT) in a cross-linked network structure formed by sodium alginate to obtain an auxiliary electrode material. The obtained auxiliary electrode material has good electrical conductivity, environmental protection and corrosion resistance. The MgO-ATP in the auxiliary electrode material has good adsorption capacity for heavy metal ions, and the Fe3O4-CNT gives the auxiliary electrode material excellent electrical conductivity. The cross-linked network structure of the auxiliary electrode material has good mechanical strength and stability.
[0020] (2) The Fe3O4-CNT in the auxiliary electrode material obtained by the present invention has magnetism. Compared with CNT / MgO-ATP / SA, the magnetism of Fe3O4 in Fe3O4-CNT / MgO-ATP / SA enables Fe3O4-CNT / MgO-ATP / SA to be magnetically adsorbed and recovered under the action of an external magnetic field; in addition to having good ferromagnetism, Fe3O4 also has good electrical conductivity. After Fe3O4 is compounded with CNT, the electrical conductivity of the obtained Fe3O4-CNT / MgO-ATP / SA is further improved, the current response in the electric repair process is enhanced, and it is helpful to further improve the efficiency of the electrochemical reaction;
[0021] (3) If the Fe3O4 in the Fe3O4-CNT / MgO-ATP / SA obtained by the present invention is replaced with Fe2O3, the obtained Fe2O3-CNT / MgO-ATP / SA has low magnetism and is not easy to collect and separate. In addition, the electrical conductivity of Fe2O3 is poor, and the removal efficiency of heavy metal contamination ions by Fe2O3-CNT / MgO-ATP / SA during the electrokinetic remediation process cannot be significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 : Schematic diagram of the test principle structure of the electric repair device adopted in the present invention.
[0023] Figure 2 : XRD comparison diagrams of the electrode materials obtained in Examples 1-3 respectively. DETAILED DESCRIPTION
[0024] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.
[0025] Example 1
[0026] (1) Weigh 20 g of ATP, add it to 100 mL of 1 mol / L MgCl·6H2O aqueous solution, stir and mix evenly, adjust the solution pH to 10 with 2 mol / L NaOH, transfer it to a polytetrafluoroethylene autoclave, and perform hydrothermal reaction at 120°C for 6 h. After the reaction is completed, cool it to room temperature, collect the solid product by centrifugation, and place it in an oven at 60°C for drying. After drying, grind and sieve to obtain a solid powder with an average particle size of 100 mesh. Place the obtained solid powder in a muffle furnace for calcination at a temperature of 500°C for 2 h. The heating rate of the muffle furnace is 10°C / min. After calcination, MgO-ATP is obtained;
[0027] (2) mixing carbon nanotubes and 5 mol / L nitric acid aqueous solution at a solid-liquid ratio of 1:4, stirring and reacting at 60° C. for 3 h, then successively filtering and washing the filtrate with distilled water until it is neutral and drying to obtain acidified carbon nanotubes;
[0028] (3) dissolving 1 g of the acidified carbon nanotubes in 100 mL of distilled water and dispersing by ultrasonic at 40° C. for 30 min to obtain an acidified carbon nanotube solution;
[0029] (4) Weigh 2.7g FeCl3·6H2O, 1g FeCl2·4H2O (Fe 3+ and Fe 2+ The molar ratio of 1g to 2:1) and 1g SDS are dispersed in 200mL distilled water in sequence, stirred and dispersed evenly, and then stirred and mixed evenly with the carbon nanotube solution obtained in step (3), and ammonia water is added dropwise at 80°C while stirring, and the dropping speed of ammonia water is 1-2s / drop. When the pH is added to 8, the reaction is stirred for 60min. After the reaction is completed, a magnet is placed in the reaction solution to absorb the solid product in the reaction solution by magnetic attraction. The solid product is washed three times with acetone and dried at 80°C for 24h, and then placed in a tubular furnace under nitrogen protection and calcined at 550°C for 1h. The heating rate of the tubular furnace is 3°C min -1 , Fe3O4-CNT is obtained;
[0030] (5) Prepare 50 mL of 10 mg / mL Fe3O4-CNT aqueous solution;
[0031] (6) Take 5 g of MgO-ATP and evenly disperse it in 50 mL of deionized water to obtain a MgO-ATP suspension;
[0032] (7) dropping all the Fe3O4-CNT aqueous solution in step (5) into the MgO-ATP suspension obtained in step (6), while adding dropwise and magnetically stirring, the dropping speed is 1-2 s / drop, after the dropping is completed, ultrasonically dispersed (ultrasonic power is 20 W) for 2 h, and then stirred (stirring speed is 500 rpm) for 6 h to obtain a Fe3O4-CNT / MgO-ATP mixed suspension;
[0033] (8) Add 50 mL of 10 g·L -1 The SA aqueous solution was added dropwise to the Fe3O4-CNT / MgO-ATP mixed suspension obtained in step (7), and the mixture was stirred at room temperature for 3 h. After the reaction, the reaction solution was filtered, and the filter cake was frozen in an ultra-low temperature refrigerator (-80°C) for 12 h, and then freeze-dried in a freeze dryer (-50°C, 10Pa) for 24 h. The obtained sample was placed in a tubular furnace and calcined at 450°C for 30 min under nitrogen protection. The heating rate of the tubular furnace was 3°C min -1, and Fe3O4-CNT / MgO-ATP / SA electrode material is obtained.
[0034] Example 2 is the same as Example 1, except that in step (5) of Example 2, the volume of the 10 mg / mL Fe3O4-CNT aqueous solution is 100 mL.
[0035] Example 3 is the same as Example 1, except that in step (5) of Example 3, the volume of the 10 mg / mL Fe3O4-CNT aqueous solution is 200 mL.
[0036] Comparative Example 1
[0037] A CNT / MgO-ATP / SA electrode material, the preparation method is as follows:
[0038] (1) Weigh 20 g of ATP, add it to 100 mL of 1 mol / L MgCl·6H2O aqueous solution, stir and mix evenly, adjust the solution pH to 10 with 2 mol / L NaOH, then transfer it to a polytetrafluoroethylene autoclave, and perform hydrothermal reaction at 120°C for 6 h. After the reaction is completed, cool it to room temperature, collect the solid product by centrifugation, and place it in an oven at 60°C for drying. After drying, grind and sieve to obtain a solid powder with an average particle size of 100 mesh. Place the obtained solid powder in a muffle furnace for calcination at a calcination temperature of 500°C for 2 h. The heating rate of the muffle furnace is 10°C / min. After calcination, MgO-ATP is obtained;
[0039] (2) mixing carbon nanotubes and 5 mol / L nitric acid aqueous solution at a solid-liquid ratio of 1:4, stirring and reacting at 60° C. for 3 h, then successively filtering and washing the filtrate with distilled water until it is neutral and drying to obtain acidified carbon nanotubes;
[0040] (3) dissolving 1 g of the acidified carbon nanotubes in 100 mL of distilled water and dispersing by ultrasonic at 40° C. for 30 min to obtain an acidified carbon nanotube solution;
[0041] (4) The acidified carbon nanotube solution obtained in step (3) is dried at 80° C. for 24 h to obtain an acidified CNT powder;
[0042] (5) preparing 50 mL of 10 mg / mL acidified CNT powder aqueous solution;
[0043] (6) Take 5 g of MgO-ATP and evenly disperse it in 50 mL of deionized water to obtain a MgO-ATP suspension;
[0044] (7) dropping all of the acidified CNT powder aqueous solution obtained in step (5) into the MgO-ATP suspension obtained in step (6), while magnetically stirring, with a dropping speed of 1-2 s / drop. After the dropping is completed, ultrasonic dispersion (ultrasonic power is 20 W) for 2 h, and then stirring (stirring speed is 500 rpm) for 6 h to obtain a CNT / MgO-ATP mixed suspension;
[0045] (8) Add 50 mL of 10 g·L -1 The SA aqueous solution was added dropwise to the CNT / MgO-ATP mixed suspension obtained in step (7), and the mixture was stirred at room temperature for 3 h. After the reaction was completed, the reaction solution was filtered, and the filter cake was frozen in an ultra-low temperature refrigerator (-80°C) for 12 h, and then freeze-dried in a freeze dryer (-50°C, 10Pa) for 24 h. The obtained sample was placed in a tubular furnace and calcined at 450°C for 30 min under nitrogen protection. The heating rate of the tubular furnace was 3°C min -1 , and the CNT / MgO-ATP / SA electrode material is obtained.
[0046] Comparative Example 2
[0047] A Fe2O3-CNT / MgO-ATP / SA electrode material, the preparation method is as follows:
[0048] (1) Weigh 20 g of ATP, add it to 100 mL of 1 mol / L MgCl·6H2O aqueous solution, stir and mix evenly, adjust the solution pH to 10 with 2 mol / L NaOH, transfer it to a polytetrafluoroethylene autoclave, and perform hydrothermal reaction at 120°C for 6 h. After the reaction is completed, cool it to room temperature, collect the solid product by centrifugation, and place it in an oven at 60°C for drying. After drying, grind and sieve to obtain a solid powder with an average particle size of 100 mesh. Place the obtained solid powder in a muffle furnace for calcination at a temperature of 500°C for 2 h. The heating rate of the muffle furnace is 10°C / min. After calcination, MgO-ATP is obtained;
[0049] (2) mixing carbon nanotubes and 5 mol / L nitric acid aqueous solution at a solid-liquid ratio of 1:4, stirring and reacting at 60° C. for 3 h, then successively filtering and washing the filtrate with distilled water until it is neutral and drying to obtain acidified carbon nanotubes;
[0050] (3) dissolving 1 g of the acidified carbon nanotubes in 100 mL of distilled water and dispersing by ultrasonic at 40° C. for 30 min to obtain an acidified carbon nanotube solution;
[0051] (4) Weigh 2.7 g of FeCl3·6H2O and 1 g of SDS and disperse them in 200 mL of distilled water in turn. After stirring and dispersing them uniformly, stir and mix them uniformly with the carbon nanotube solution obtained in step (3). Add ammonia water dropwise at 80°C while stirring. The ammonia water is added at a rate of 1-2 s / drop. When the pH is reached to 8, stir and react for 60 min. After the reaction is completed, place a magnet in the reaction solution to absorb the solid product in the reaction solution by magnetic attraction. The solid product is washed three times with acetone and dried at 80°C for 24 h. It is placed in a tubular furnace under nitrogen protection and calcined at 550°C for 1 h. The heating rate of the tubular furnace is 3°C min -1 , Fe2O3-CNT is obtained;
[0052] (5) Prepare 50 mL of 10 mg / mL Fe2O3-CNT aqueous solution;
[0053] (6) Take 5 g of MgO-ATP and evenly disperse it in 50 mL of deionized water to obtain a MgO-ATP suspension;
[0054] (7) dropping all the Fe2O3-CNT aqueous solution in step (5) into the MgO-ATP suspension obtained in step (6), while magnetically stirring, the dropping speed is 1-2s / drop, after the dropping is completed, ultrasonically dispersed (ultrasonic power is 20W) for 2h, and then stirred (stirring speed is 500rpm) for 6h to obtain a Fe2O3-CNT / MgO-ATP mixed suspension;
[0055] (8) Add 50 mL of 10 g·L -1 The SA aqueous solution was added dropwise to the Fe2O3-CNT / MgO-ATP mixed suspension obtained in step (7), and the mixture was stirred at room temperature for 3 h. After the reaction, the reaction solution was filtered, and the filter cake was frozen in an ultra-low temperature refrigerator (-80°C) for 12 h, and then freeze-dried in a freeze dryer (-50°C, 10Pa) for 24 h. The obtained sample was placed in a tubular furnace and calcined at 450°C for 30 min under nitrogen protection. The heating rate of the tubular furnace was 3°C min -1 , and Fe2O3-CNT / MgO-ATP / SA electrode material is obtained.
[0056] The XRD patterns of the electrode materials obtained in Examples 1-3 are shown in the attached manual. Figure 2As shown, the test results show that the electrode materials obtained in Examples 1-3 respectively have Fe3O4 (220), (422) and (440) crystal plane peaks at 2θ=29.6°, 53.8° and 62.1°, CNT (002) and (100) crystal plane peaks at 26.6° and 42.7°, MgO (111), (310) and (222) crystal plane peaks at 2θ=27.8°, 73.5° and 76.6°, APT (110), (130), (040), (400) and (161) crystal plane peaks at 2θ=5.8°, 17.8°, 19.8°, 21.8° and 36.1°. The XRD characteristic peaks of sodium alginate are not obvious because it is an amorphous polymer, which usually shows broad and disordered diffraction peaks.
[0057] Performance Testing
[0058] The electrode materials obtained in Examples 1-3 and Comparative Example 1 were subjected to an experiment on the effect of electrokinetic repair to remove heavy metal particles in the soil. The specific test method is as follows:
[0059] The electric repair device used in the experiment is exactly the same as the conventional electric repair device in the field. The specific test principle diagram is shown in the attached manual. Figure 1 As shown, the device includes a soil remediation chamber (dimensions length × width × height = 15cm × 10cm × 10cm), a cathode chamber (dimensions length × width × height = 5cm × 10cm × 10cm), an anode chamber (dimensions length × width × height = 5cm × 10cm × 10cm), an adjustable DC voltage-stabilized power supply, two high-purity graphite electrode plates (dimensions length × width × thickness = 10cm × 10cm × 1cm), a cathode electrolyte is a mixed solution of 1 mol / L citric acid aqueous solution (CA) and 0.02 mol / L sodium dodecyl sulfate aqueous solution (SDS) in a volume ratio of 1: 1, and an anolyte is 1 mol / L citric acid aqueous solution (CA). Among them, the electrode materials obtained in Examples 1-3 and Comparative Examples 1-2 were respectively used as auxiliary electrode sheets (dimensions length × width × thickness = 5cm × 3.5cm × 0.2cm) of the electric remediation device after tabletting, and assembled to form 5 different electric remediation devices (only the type of auxiliary electrode sheets is different), and tested under the same experimental conditions. The height of the cathode electrolyte or the anode electrode liquid is the same as the height of the heavy metal contaminated soil sample in the soil remediation chamber. The auxiliary electrode is placed between the soil and the cathode chamber or the anode chamber and wrapped with fiber filter paper, and then fixed with a perforated organic glass plate. The soil remediation chamber and the cathode chamber or the anode chamber are separated by a composite membrane formed by perforated organic glass and filter paper. The pore diameter of the perforated organic glass surface is 1 mm, the pore density is 9 holes per square centimeter, and the filter paper is a medium-speed filter paper with a pore diameter of 30 μm.
[0060] The principle of the electric repair experimental test is as follows:
[0061] During the experiment, a homemade 600g heavy metal contaminated soil sample was placed in a soil remediation chamber and compacted evenly. The high-purity graphite electrode plate was energized through a wire by an adjustable DC regulated power supply in the electric remediation device. Under the action of the electric field, the cadmium and zinc metal ions in the heavy metal contaminated soil sample migrated to the cathode chamber by electromigration or electroosmosis. After the reaction was completed, the soil in the soil remediation chamber was purified.
[0062] Referring to "HJ832-2017 Microwave Digestion Method for Total Metal Elements in Soil and Sediment", in this experiment, the samples were digested with hydrochloric acid (HCl)-perchloric acid (HClO4)-hydrofluoric acid (HF)-nitric acid (HNO3). The digestion process was completed using an acid remover and a microwave digester. After dilution, the content of heavy metals in the electroremediation contaminated soil was determined using a flame atomic absorption spectrophotometer.
[0063] The preparation method of heavy metal contaminated soil samples is as follows:
[0064] The heavy metal pollutants were selected as cadmium nitrate and zinc nitrate. 826.26 mg of cadmium nitrate and 6.82 g of zinc nitrate were dissolved in 500 mL of deionized water. The heavy metal solutions were added to 3 kg of soil successively, and the moisture content was maintained at 30%. The soil was stirred for 10 minutes every 2 hours, and stirred 4 times in total to promote the uniform distribution of heavy metal ions in the soil. The prepared contaminated soil samples were placed in a fume hood for 60 days, and stored for use after the water in the contaminated soil samples evaporated completely to obtain heavy metal contaminated soil samples. The Cd 2+ The initial concentration was 76.58 mg / kg, Zn 2+ The initial concentration was 320.38 mg / kg.
[0065] During the test, the graphite electrode plate was used as the main electrode, the materials of Examples 1-3 and Comparative Examples 1-2 were used as auxiliary electrode sheets, the voltage gradient was 1.5 V / cm, and the repair time was 7 days. The test results are shown in Table 1.
[0066] Table 1
[0067] Test items <![CDATA[Cd after treatment 2+ Concentration (mg / kg)]]> <![CDATA[Cd 2+ Removal rate (%)]]> <![CDATA[Zn after treatment 2+ Concentration (mg / kg)]]> <![CDATA[Zn 2+ Removal rate (%)]]> Example 1 27.18 64.51 136.75 57.32 Example 2 10.58 86.18 87.95 72.55 Example 3 19.45 74.60 102.27 68.08 Comparative Example 1 43.92 42.65 189.92 40.72 Comparative Example 2 36.59 52.22 167.56 47.70
[0068] Note: The treated Cd in Table 1 2+ The concentration refers to the Cd content in the heavy metal contaminated soil samples after electrokinetic remediation. 2+ Concentration; Zn after treatment 2+ The concentration refers to the Zn content in the heavy metal contaminated soil samples after electrokinetic remediation. 2+ concentration.
[0069] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A Fe3O4-CNT / MgO-ATP / SA electrode material, characterized in that: The preparation method comprises the following steps: (1) ATP powder and soluble magnesium salt undergo hydrothermal reaction under alkaline conditions, the reaction liquid is separated into solid-liquid to obtain a solid product, and the obtained solid product is placed at high temperature and calcined in an air atmosphere to obtain MgO-ATP loaded with magnesium oxide particles; (2) The acidified carbon nanotubes and Fe 2+ , Fe 3+ The soluble salt and the surfactant are mixed evenly in the aqueous solution, the pH of the solution is adjusted to be alkaline, and the reaction is stirred until the iron oxide is adsorbed on the tube wall of the acidified carbon nanotube, and the solid product in the solution is collected by magnetic attraction using a magnet to obtain Fe3O4-CNT; (3) mixing and dispersing MgO-ATP and Fe3O4-CNT in deionized water to obtain a Fe3O4-CNT / MgO-ATP suspension; (4) The SA aqueous solution is added dropwise to the Fe3O4-CNT / MgO-ATP suspension while stirring. After the reaction is completed, the reaction solution is filtered, and the obtained filter cake is freeze-dried and heat-treated at high temperature under a nitrogen atmosphere.
2. The Fe3O4-CNT / MgO-ATP / SA electrode material according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (1) is not less than 120° C., and the hydrothermal time is not less than 6 hours.
3. The Fe3O4-CNT / MgO-ATP / SA electrode material according to claim 1, characterized in that: The high temperature calcination temperature in step (1) is not higher than 500° C., and the calcination time is not less than 2 hours.
4. The Fe3O4-CNT / MgO-ATP / SA electrode material according to claim 1, characterized in that: The acidified carbon nanotubes in step (2) are products obtained by adding carbon nanotubes to a dilute nitric acid aqueous solution for oxidation.
5. The Fe3O4-CNT / MgO-ATP / SA electrode material according to claim 1, characterized in that: The surfactant is SDS.
6. The Fe3O4-CNT / MgO-ATP / SA electrode material according to claim 1, characterized in that: In step (3), the mass ratio of MgO-ATP to Fe3O4-CNT is 0.1-2:
1.
7. The Fe3O4-CNT / MgO-ATP / SA electrode material according to claim 6, characterized in that: In step (3), the mass ratio of MgO-ATP to Fe3O4-CNT is 1:
1.
8. The Fe3O4-CNT / MgO-ATP / SA electrode material according to claim 7, characterized in that: The mass ratio of SA in step (4) to MgO-ATP and Fe3O4-CNT in step (3) is 1:1:
1.
9. The Fe3O4-CNT / MgO-ATP / SA electrode material according to claim 1, characterized in that: The temperature of the high temperature heat treatment in step (4) is not higher than 450°C, and the heat treatment time is not less than 2 hours.
10. The Fe3O4-CNT / MgO-ATP / SA electrode material according to claim 1, characterized in that: The freeze-drying time in step (4) is not less than 24 hours.
Citation Information
Patent Citations
High-durability fuel cell membrane electrode and preparation method
CN101789509A
Super-capacitor electrode made of attapulgite and manufacturing method thereof
CN103413688A
Nano magnetic environmental remediation material with Fe3O4 supported on attapulgite and used for removing organic pollutants as well as preparation method of material
CN106268812A
Composite electrode for electro-kinetic remediation of heavy metal contaminated soil, electro-kinetic remediating device and electro-kinetic remediation method
CN106378357A
Preparation method of iron tetroxide-carbon nanotube lithium battery negative electrode material
CN109119625A